The magic bird : folk tales from China (Beijing : Foreign Languages Press, 1985)
The thirteen stories in this book are taken from nine distinct traditions-the Han, the Uygur, the Mongolian, the Tibetan, the Naxi, the Hui, the Kazak, the Yugur and the Dong nationalities. Enter their world and learn of the mighty hero Kandebay who defeated the wicked Fairy King, the Long-haired Girl who sacrificed her life for her people, and two young lovers, herding their sheep on the steppes. Meet the quick-witted fox, the bird who loves to tell stories, and many, many others, all illustrated with delightful drawings.
Li Bao and Cui Cui (Han Nationality) -- The Golden-haired Boy (Uygur Nationality) -- Xiawudong, the Fisherman's Son (Uygur Nationality) -- Hailibu the Hunter (Mongolian Nationality) -- The Clever Red Fox (Mongolian Nationality) -- The Magic Bird (Mongolian Nationality) The Shell Girl (Tibetan Nationality) -- Zhugu and Kangmei (Naxi Nationality) -- Hengmei and the Golden Deer (Naxi Nationality) -- Big Xue and Silver Bell (Hui Nationality) -- Kandebay the Hero (Kazak Nationality)
Koleksi Sumbangan : Dr. Syed Husin Ali
Keywords: Tales -- China -- Juvenile literature; Folklore -- China